Comparative of the complete chloroplast genome and RNA editing of Eucalyptus camaldulensis T5 clone, an elite variety in Thailand - PHRUET RACHARAK; ANONGPAT SUTTANGKAKUL; SUPACHAI VUTTIPONGCHAIKIJ (Society for Indonesian Biodiversity, 2023)
Abstract. Racharak P, Suttangkakul A, Vuttipongchaikij S. 2023. Comparative of the complete chloroplast genome and RNA editing of Eucalyptus camaldulensis T5 clone, an elite variety in Thailand. Biodiversitas24: 3774-3784. Eucalyptus camaldulensis, T5 clone, the excellent fast-growing tree plantation in Thailand, was analyzed for the complete chloroplast genome and RNA editing. The complete chloroplast genome revealed a total genome size of 160,204 bp that divided into a large single copy (LSC) (88,904 bp) and a small single copy region (SSC) (18,506 bp) by inverted repeat regions (IR) containing 26,397 bp. A circular mapping genome and gene order showed the circle antiparallel mapping gene of 135 genes, including 37 tRNAs, 10 rRNAs, and 1 pseudogene. GC content of the genome was 36.87%. The comparative genomes analysis between the T5 clone and E. camaldulensis from the NCBI database suggested that the thymine (T) and adenine (A) strongly impacted the indel and transversion process, which could be a point of mutation in the genome. Furthermore, 24 specific genes were used to investigate RNA editing. From all genes, only 11 genes were edited with C to U conversion.Triplet codons, tUA, tUt, tUg and Ugg were the most frequently edited codon and expressions; the crucial influence of amino acid alterations. Due to RNA editing events, the physicochemical properties of amino acids were changed from polar to nonpolar amino acids and from hydrophilic to hydrophobic amino acids. Physicochemical properties conversion is necessary to form complete amino acid sequences for several essential chloroplast proteins. The event might be the accumulation of amino acid alterations causing phenotypic variation for plant adaptation and evolution.